Admission: Madness and (Be)coming Out Within and Through Spaces of Confinement - Jennifer Eisenhauer (Disability Studies Quarterly, 2009)
This article examines, through a performative narrative, an installation artwork that I created in May 2008 titled Admission. This artwork and reflective writing embodies a form of creative inquiry into issues surrounding and the intersections of (be)coming out, nonvisible disabilities, and representations of mental illness. Deleuze and Guattari's concepts of becoming and the rhizome inform my investigation into (be)coming out, not as an event thought of as a singular moment defined through a fixed notion of the subject, but as an ongoing process of creating connections between subjects understood as multiplicities. In its conclusions, this article proposes that the kind of inquiry characteristic of artmaking can offer unique opportunities for understanding the complexities of the intersections of subjectivity and (be)coming out as a person with a mental illness